2000
DOI: 10.1007/s00276-000-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Arterial vascularisation of the atrioventricular node

Abstract: The aim of this study was to define the anatomic characteristics of the principal arterial source of the atrioventricular node, known as the artery of the atrioventricular node. Forty hearts were studied by various anatomic and radiologic methods: dissection, injection-dissection, injection-corrosion and injection-radiography, but only 23 results were interpretable. The right coronary artery represented the commonest arterial source of the atrioventricular node (21/23 hearts) but numerous variations in the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In 80-87% of patients, atrioventricular nodal artery arises from distal RCA and penetrates to the posterior interatrial septum base at the level of heart crux. In the remaining patients, it arises from terminal part of LCX (8-13%) or rarely from left anterior descending artery (2-10%) [2,3,24]. Pejković et al [21] defined AVNA as the first and the longest inferior septal perforator branch that usually arose from RCA (90%) and infrequently from LCX artery (10%).…”
Section: Discussionmentioning
confidence: 99%
“…In 80-87% of patients, atrioventricular nodal artery arises from distal RCA and penetrates to the posterior interatrial septum base at the level of heart crux. In the remaining patients, it arises from terminal part of LCX (8-13%) or rarely from left anterior descending artery (2-10%) [2,3,24]. Pejković et al [21] defined AVNA as the first and the longest inferior septal perforator branch that usually arose from RCA (90%) and infrequently from LCX artery (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Left‐sided origin results in traversing in front of cardiac sulci through the inferior atrioventricular sulcus, near the opening of the coronary sinus, towards the Koch's triangle apex, as found in a previous study by Sow et al (1996). As the course of the AVNA is highly variable, another study performed by Adrid et al (2000) found the AVNA's course to be proximal to the tricuspid valve's septal cusp as well as the aortic ring.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5028 articles were initially evaluated by two independent reviewers. Eventually, 33 articles met the required criteria and were used in this meta‐analysis (James & Burch, 1958; Romhilt et al, 1968; Vieweg et al, 1975, 1982; Hutchinson, 1978; Anderson & Murphy, 1983; Brugada et al, 1990; Wang et al, 1990; Sneddon et al, 1991; Burke et al, 1993; Krupa, 1993; Sow et al, 1996; Arid et al, 2000; Lin, 2000; Sanchez‐Quintana et al, 2001; Futami et al, 2003; Kaplana, 2003; Berdajs et al, 2008; Pejković et al, 2008; Saremi et al, 2008; Nerantzis et al, 2009; Paulsen & Vetner, 2009; Ramanathan et al, 2009; Rusu et al, 2009; Ballesteros et al, 2010; El‐Maasarany et al, 2010; Cezlan et al, 2012; Kazemisaeid et al, 2012; Sabnis & Silotry, 2012; Verma et al, 2014; Divyaprakash et al, 2016; Kawashima & Sato, 2018; Iwanaga et al, 2023). The overall data collection process can be found in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Arid et al also found, in 33,33% of the specimens with "right coronary dominance" (there was made no distinction with the hyperdominance), the AVNA leaving "from the terminal part of the right coronary a., as well as the left retroventricular a. and the posterior interventricular a. thus forming a sort of trifurcation" -in our study we defined as trifurcated only the arteries (RCA's, type IV) with adjacent origins of the PIVA, left RVA and AVNA and if the AVNA emerged from the initial part of the RVA or the PIVA we considered that artery as origin (types II and III) and didn't take the RCA branching pattern as trifurcation. Moreover, Arid et al didn't found any specimen with the AVNA leaving the Uturn of the RCA, with left RVA absent [5].…”
Section: Discussionmentioning
confidence: 99%